Exploring different heuristics for WSN localization based on trilateration - Jovanov, Andrej; Stoimenov, Robert; Risteska Stojkoska, Biljana (My University, 2018)
Localization remains a challenging problem in wireless sensor networks community. There are many algorithms for localization proposed in the literature, ranging from very basic to very complex. Among them, trilateration is one of the oldest and simplest approach, that can be used alone, or as part of more complex pipelines. In this paper we explore two different heuristics that adopt trilateration as a base technique. Our heuristics use distance information together with knowledge about the most appropriate anchors in terms of quality. We show that by improving trilateration with different heuristics, localization error can be significantly reduced, while maintaining low computational cost.
Keywords: localization; wireless sensor network; trilateration; heuristics